Critical Challenges to Albanian Higher Education and Its Internationalization - Skendaj, lton; de Wit, Hans (International Higher Education, 2025)
This article describes and analyzes the development and internationalization of higher education in Albania since 1991, when a 45-year long dictatorial period ended. It considers the major developments and challenges in the context of Albania’s efforts toward European integration and internationalization.